Isolation And Characterization Of A Novel Bacterium, Bacillus Thuringiensis Var. Israelensis Vcrc-B651 Exhibiting High Efficacy To Controlmosquito Vectors (Applied Biological Research, 2023)
The aim of this study was to isolate novel mosquitocidal bacteria from clayey  soil. The soil samples were collected during the period 2021 to 2022 from an  agricultural field of Tamil Nadu (India). The samples were processed for  isolating the bacteria on nutrient yeast extract salt medium. The bacterial cell mass was harvested after 72 h of lyophilisation. Bioassay was carried out with  the bacterium against larval species of Culex quinquefasciatus, Aedes aegypti and  Anopheles stephensi. Whole genome sequence (WGS) analysis (Illumina) was done to identify the strain. Growth dynamics, biochemical characteristics, and toxicity assays with non-target aquatic organisms were also done. Based onWGS  analysis the new isolate was identified as Bacillus thuringiensis serovar  israelensis. The strain was coded as VCRC-B651. The isolate exhibited effective toxicity against A. aegypti, A.stephensi, and C. quinquefasciatus with LC50 values of 0.005, 0.009 and 0.009 mg L-1, respectively, and LC90 values of 0.009, 0.02 and 0.018 mg L-1, respectively. The isolate exhibited higher mosquitocidal activity as compared to the WHO reference strain (Bti H14). No adverse effect on aquatic non-target organisms was observed. The new isolate was highly efficacious in controlling the mosquito larvae.
Keywords: Bacillus thuringiensis serovar israelensis; bioassays; clay soil; growth dynamics; mosquito larvae; whole genome sequence